It is the change that matters - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Impact Assessment for Development Agencies: Learning to Value Change. C Roche. An Oxfam Development Guideline, co-published with Novib. 1999. 160 pp. ISBN 0 85598 418 X GBP 9.95 16.45 Oxfam Publishing 274 Banbury Road Oxford OX2 7DZ, UK Fa